2003
DOI: 10.1038/sj.gt.3302011
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant AAV serotype 1 transduction efficiency and tropism in the murine brain

Abstract: Recombinant adeno-associated virus serotype 2 (rAAV2) vectors have shown promise as therapeutic agents for neurologic disorders. However, intracerebral administration of this vector leads to preferential transduction of neurons and a restricted region of transgene expression. The recently developed rAAV vectors based upon nonserotype 2 viruses have the potential to overcome these limitations. Therefore, we directly compared a rAAV type 1 to a type 2 vector in the murine brain. The vectors were engineered to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(80 citation statements)
references
References 39 publications
7
73
0
Order By: Relevance
“…This positive staining was gradually reduced with new vessel development (k, 3 weeks and l, 5 weeks), suggesting that astrocytes played a supportive role during the neovascularization. In addition, CD31 (m, n) and a-actin finding that neurons and astrocytes are transducible by the recombinant AAV1 vectors (Tenenbaum et al, 2004;Wang et al, 2003). Similar to in vitro studies, the infected cells (neurons and astrocytes) expressed and secreted functional netrin-1 and acted on cells in brain tissue, including endothelial cells.…”
Section: Discussionmentioning
confidence: 59%
“…This positive staining was gradually reduced with new vessel development (k, 3 weeks and l, 5 weeks), suggesting that astrocytes played a supportive role during the neovascularization. In addition, CD31 (m, n) and a-actin finding that neurons and astrocytes are transducible by the recombinant AAV1 vectors (Tenenbaum et al, 2004;Wang et al, 2003). Similar to in vitro studies, the infected cells (neurons and astrocytes) expressed and secreted functional netrin-1 and acted on cells in brain tissue, including endothelial cells.…”
Section: Discussionmentioning
confidence: 59%
“…In order for such an approach to be clinically effective, it seemed likely that widespread expression in target regions of the brain, cortex, and striatum would be needed. It has been reported that the transduction efficiency in the CNS of AAV1 is superior to that of AAV2 in various animal models, including mouse, rat, and cat (Vite et al, 2003;Wang et al, 2003;Burger et al, 2004). Significantly, however, there is to our knowledge no published report of AAV1 in the primate brain.…”
Section: Introductionmentioning
confidence: 68%
“…A number of reports have shown that the AAV1 serotype transduces the brain more efficiently than does AAV2 (Vite et al, 2003;Wang et al, 2003;Dodge et al, 2005). We have explored in nonhuman primates the utility of this serotype with a vector that encodes a humanized Renilla green fluorescent protein (hrGFP) for which the codon usage has been optimized for use in mammals (see patent WO=2004=005322).…”
Section: Discussionmentioning
confidence: 99%
“…AAV2 has shown higher transduction efficiency in glioblastoma in vitro and in vivo when compared to serotypes 4 and 5 [183]. However, other studies have demonstrated a higher distribution and transduction in the CNS when using rAAV serotypes 1 and 5 [175, 184, 185]. The different AAV serotypes have been exploited on their ability to efficiently transduce distinct regions of the brain due to different cellular tropisms [174, 183, 186].…”
Section: Aav Based Vectorsmentioning
confidence: 99%